Utilización de técnicas cognitivo-conductuales para la disminución de ansiedad asociada a estrés laboral en los funcionarios de 45 a 55 años, que acuden al área de psicología del dispensario médico matriz Quito de la Empresa Pública Petroecuador durante el período de octubre 2016-marzo 2017. - López Soria, Sued Ismael (2017)
The following systematization of experiences details the process of therapeutic intervention executed with the “Empresa Pública Petroecuador” workers, through October 2016 to March 2017. The results show symptoms of anxiety associated to work-related stress to be the predominant issue, which is why techniques based on the Cognitive-Behavioral were needed and thus implemented, aiming to reduce the preciously diagnosed symptomatology. The project was targeted to six workers within a 45 to 55 age range, in a total of ten to twelve sessions. The ISRA test (Inventario de Situaciones y Respuestas de Ansiedad) (Miguel & Cano, 2007) (it means, Anxiety Situations and Responses inventory) was used to thoroughly evaluate the participants. It enabled a specification of the anxiety type and level of intensity predominated, hence, allowing the development of anxiety responses profiles which enabled the selection of the most appropriate techniques. These Cognitive-Behavioral techniques, exercises and strategies where developed with each patient, were well received by the workers and through their constant practice, at the end of the therapeutic intervention, it was possible to evidence significant changes in the final results. The systematization focused on the learning and understanding of the experience obtained by applying Cognitive-Behavioral techniques for the reduction of anxiety, through analysis of results, opportunities, and difficulties that were found throughout the intervention process.